Brain white matter microstructure is associated with susceptibility to motion‐induced nausea. Issue 5 (29th January 2013) - Napadow, V.; Sheehan, J.; Kim, J.; Dassatti, A.; Thurler, A. H.; Surjanhata, B.; Vangel, M.; Makris, N.; Schaechter, J. D.; Kuo, B.
Abstract Nausea is associated with significant morbidity, and there is a wide range in the propensity of individuals to experience nausea. The neural basis of the heterogeneity in nausea susceptibility is poorly understood. Our previous functional magnetic resonance imaging (fMRI) study in healthy adults showed that a visual motion stimulus caused activation in the right MT+/V5 area, and that increased sensation of nausea due to this stimulus was associated with increased activation in the right anterior insula. For the current study, we hypothesized that individual differences in visual motion‐induced nausea are due to microstructural differences in the inferior fronto‐occipital fasciculus (IFOF), the white matter tract connecting the right visual motion processing area (MT+/V5) and right anterior insula. To test this hypothesis, we acquired diffusion tensor imaging data from 30 healthy adults who were subsequently dichotomized into high and low nausea susceptibility groups based on the Motion Sickness Susceptibility Scale. We quantified diffusion along the IFOF for each subject based on axial diffusivity (AD); radial diffusivity (RD), mean diffusivity (MD) and fractional anisotropy (FA), and evaluated between‐group differences in these diffusion metrics. Subjects with high susceptibility to nausea rated significantly (P < 0.001) higher nausea intensity to visual motion stimuli and had significantly (P < 0.05) lower AD and MD along the right IFOF compared to subjects with low susceptibility to nausea. This result suggests that differences in white matter microstructure within tracts connecting visual motion and nausea‐processing brain areas may contribute to nausea susceptibility or may have resulted from an increased history of nausea episodes.